A Systematic Literature Review of Internal Auditing in Public Sector Finance - Nasution, Dito Aditia Darma; Napitupulu, Juni Yanti; Buaya, Register Launli (RIGGS: Journal of Artificial Intelligence and Digital Business, 2025)
This study reviews the literature from the past 10 years, from 2015 to 2024, on public sector financial internal auditing (IA) and addresses three interrelated research questions (RQ): How has research on public sector IA evolved? What are the main focuses and critiques of the public sector IA literature? What is the future direction for public sector IA research?. We adopted a systematic literature review approach and analyzed 78 peer-reviewed journal articles. We evaluated five criteria to identify the development of public sector IA research (RQ1), namely level of government, academic discipline, number of countries, geographic region, and MSCI country classification. Similarly, we used four criteria to present the focus and critique of the literature (RQ2), namely, type of organizational respondents, research instruments, theories, and research themes examined. Finally, we used two criteria to propose new directions for future research (RQ3), namely, directions generated from RQ1 and RQ2 and directions highlighted by the 10 most cited studies in the IA literature (i.e., from the 78 identified papers). We observed a rise in publications up to 2023, most of which focused on single-country studies, particularly in emerging markets. Furthermore, we noted that IA has been studied at all levels of government, most frequently at the local government level. While we identified several research themes in the literature, most studies emphasized "governance" and "operational effectiveness" using quantitative analysis, often without reference to any theoretical framework.